Reliability and Usefulness of Intraoperative 3-Dimensional Imaging by Mobile C-Arm With Flat-Panel Detector. Issue 1 (February 2017) - Fujimori, Takahito; Iwasaki, Motoki; Nagamoto, Yukitaka; Kashii, Masafumi; Takao, Masaki; Sugiura, Tsuyoshi; Yoshikawa, Hideki
Abstract : Study Design: Reliability and agreement study. Objective: To assess the reliability of intraoperative 3-dimensional imaging with a mobile C-arm (3D C-arm) equipped with a flat-panel detector. Summary of Background Data: Pedicle screws are widely used in spinal surgery. Postoperative computed tomography (CT) is the most reliable method to detect screw misplacement. Recent advances in imaging devices have enabled surgeons to acquire 3D images of the spine during surgery. However, the reliability of these imaging devices is not known. Methods: A total of 203 screws were used in 22 consecutive patients who underwent surgery for scoliosis. Screw position was read twice with a 3D C-arm and twice with CT in a blinded manner by 2 independent observers. Screw positions were classified into 4 categories at every 2 mm and then into 2 simpler categories of acceptable or unacceptable. The degree of agreement with respect to screw positions between the double readings was evaluated by κ value. With unanimous agreement between 2 observers regarding postoperative CT readings considered the gold standard, the sensitivity of the 3D C-arm for determining screw misplacement was calculated. Results: A total 804 readings were performed. For the 4-category classification, the mean κ value for the 2 interobserver readings was 0.52 for the 3D C-arm and 0.46 for CT. For the 2-category classification, the mean κ value for the 2 interobserver readings was 0.80 for the 3D C-arm and 0.66 for CT. The sensitivity, specificity, positive predictive value, and negative predictive value of intraoperative imaging with the 3D C-arm were 70%, 95%, 44%, and 98%, respectively. With respect to screws with perforation ≥4 mm, the sensitivity was 83%. No revision surgery was performed. Conclusions: Intraoperative imaging with a 3D C-arm was reliable for detecting screw misplacement and helpful in decreasing the rate of revision surgery for screw misplacement.